A 52-to-67 GHz Dual-Core Push-Push VCO in 40-nm CMOS - Issakov, Vadim; Rimmelspacher, Johannes; Trotta, Saverio; Tiebout, Marc; Hagelauer, Amelie Marietta; Weigel, Robert (European Microwave Conference, 2017)
We present a continuously tunable 52-to-67 GHz push-push dual-core voltage-controlled oscillator (VCO) in a 40 nm bulk CMOS technology. The circuit is suitable for 60 GHz FMCW radar applications requiring a continuously tunable ultra-wide modulation bandwidth. The LC-tank inductor is used to couple the two VCO cores. The fundamental frequency of the VCO can be tuned from 26 GHz to 33,5 GHz, which corresponds to a frequency tuning range (FTR) of 25%. The second harmonic is extracted in a non-invasive way using a transformer. The primary side acts simultaneously as a second harmonic filter. The VCO achieves in measurement a low phase noise of 91,8 dBc=Hz at 1 MHz offset at 62 GHz and an output power of 20 dBm. The VCO including buffers dissipates in the dual-core operation mode 60 mA from a single 1,1 V supply and consumes a chip area of 0,58 mm2.
Keywords: millimeter-wave; ultra-wideband; CMOS technology